2012
DOI: 10.1017/s002237781200058x
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of geodesic acoustic mode continuum by drift wave turbulence

Abstract: Excitation of the geodesic acoustic mode continuum by drift wave turbulence is studied using the wave kinetic approach. For a model profile of weak non-uniform ion temperature, the forms of growth rate and radial structure of geodesic acoustic modes are obtained analytically. The growth rate is analyzed for several conditions for present-day tokamaks and compared with that for uniform ion temperature, as well as that given by the coherent mode approach for non-uniform ion temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The parametric GAM drive by DWs was generalized to include the radial propagation in a non-uniform plasma and dispersion effects [142,148,225,226]. The analysis in [142,148] has shown that nonlinearly excited GAMs propagate at a group velocity much larger than that predicted by linear theory, and also show the nonlinear shift of the GAM frequency due to the finite amplitude of the DW pump wave.…”
Section: Gam Generation By Reynolds Stressmentioning
confidence: 99%
“…The parametric GAM drive by DWs was generalized to include the radial propagation in a non-uniform plasma and dispersion effects [142,148,225,226]. The analysis in [142,148] has shown that nonlinearly excited GAMs propagate at a group velocity much larger than that predicted by linear theory, and also show the nonlinear shift of the GAM frequency due to the finite amplitude of the DW pump wave.…”
Section: Gam Generation By Reynolds Stressmentioning
confidence: 99%
“…The nonlinear excitation of GAM by DWs can be described by a parametric decay instability [111,112], where pump DW resonantly decay into a GAM and another DW. GAM nonlinear excitation by DW has been investigated by analytical theory [12,46,[113][114][115][116][117][118][119], numerical simulation [120][121][122][123][124][125][126][127]. The underlying three-wave interactions has also been observed experimentally [23,[128][129][130].…”
Section: Nonlinear Gam Excitation By Dwsmentioning
confidence: 99%
“…7,9 The excitation of GAM by DW turbulence has been investigated using the paradigm of parametric decay instability in several earlier works. [12][13][14][15][16][17][18][19] However, in these works, the excitation of GAM is investigated either ignoring the plasma nonuniformities or the contribution of kinetic dispersiveness. As we will show in this work, plasma nonuniformities, such as the nonuniformity of diamagnetic frequency x * (r) and/or GAM continuum, 7,20 and the finite linear group velocities of GAM and DW sideband, due to the kinetic dispersiveness, play important roles in the excitation of GAM and qualitatively change the features of parametric decay instability.…”
Section: Introductionmentioning
confidence: 99%